A Novel Strategy for Constructing 3D Dislocated Chiral Metamaterial with Negative Poisson's Ratio. Issue 3 (23rd December 2020) - Zhong, Rongchang; Zheng, Binbin; Fu, Minghui
Abstract : Metamaterials with negative Poisson's ratio (NPR) have a broad range of application background, such as aerospace engineering, automotive engineering, medical instrument engineering, and wearable engineering. Herein, a novel strategy for constructing 3D dislocated chiral metamaterial is proposed that can achieve NPR effect in three directions. According to this strategy, a new dislocated chiral metamaterial composed of dislocated tetrachiral honeycombs and inclined rods is designed and selected as an example to investigate the effectiveness of the strategy. Experiments and numerical simulations are carried out to study the mechanical properties of the new metamaterial, confirming that this metamaterial exhibits NPR effect. The influence of geometric parameters on the elastic constants of the metamaterial is discussed based on experimental and numerical results. Meanwhile, the local loading performances of this dislocated chiral metamaterial and the previous aligned chiral metamaterial are studied and compared. Results show that this dislocated metamaterial possesses a stronger damage resistance capacity than the aligned one. By adjusting the rotational direction of ligaments in honeycombs and the arrangement of inclined rods, more special 3D dislocated chiral metamaterials with advanced properties are available, such as metamaterial with both positive and NPRs, metamaterial with compression–torsion effect. Abstract : A novel strategy for constructing 3D dislocated chiral metamaterial with negative Poisson's ratio is first proposed. Experiments and numerical simulations are conducted to investigate the mechanical properties of the metamaterial. Elastic constants of the metamaterial can be tuned by designing geometric parameters. Compared with the aligned metamaterial, the dislocated metamaterial possesses more balanced Poisson's ratio and stronger damage resistance capacity.